Elastic Light Scatter Pattern Analysis for the Expedited Detection of Yersinia Species in Pork Mince: Proof of Concept - On, Stephen L. W.; Zhang, Yuwei; Gehring, Andrew; Patsekin, Valery; Chelikani, Venkata; Flint, Steve; Wang, Haoran; Billington, Craig; Fletcher, Graham C.; Lindsay, James; Robinson, J. Paul (Frontiers in Microbiology, 2021)
Isolation of the pathogens Yersinia enterocolitica and Y. pseudotuberculosis from foods typically rely on slow (10-21 day) “cold enrichment” protocols before confirmed results are obtained. We describe an approach that yields results in 39 hours that combines an alternative enrichment method with culture on a nonselective medium, and subsequent identification of suspect colonies using Elastic Light Scatter (ELS) analysis. A prototype database of ELS profiles from five Yersinia species and six other bacterial genera found in pork mince was established, and used to compare similar profiles of colonies obtained from enrichment cultures from pork mince samples seeded with representative strains of Y. enterocolitica and Y. pseudotuberculosis. The presumptive identification by ELS using computerised or visual analyses of 83/90 colonies in these experiments as the target species was confirmed by partial 16S rDNA sequencing. In addition to seeded cultures, our method recovered two naturally occurring Yersinia strains. Our results indicate that modified enrichment combined with ELS is a promising new approach for expedited detection of foodborne pathogenic yersiniae.